Re-Examining Intimate Partner Violence: Feminist Social Work Reflections - Meenu Anand; Gunjan Chandhok (Social Work and Society)
Intimate partner violence has been one of the foremost public health problems and a violation of women's human rights impacting one in three women worldwide (UN Women, 2020). Offering an insight into and questioning the concomitant edifices of violence inherent within the intimate marital relationships, the authors put forth arguments to interrogate the unique factors that impact women’s experiences and understandings of the abuse and demonstrate how gendered discourses function to polarize women’s sexuality.